Bank Privatization in Argentina : A Model of Political Constraints and Differential Outcomes - Clarke, George R.G.; Cull, Robert (World Bank, Washington, DC, 2014)
Based on results from country case studies, many researchers have claimed that political constraints affect bank privatization transactions, which in turn affect the post-privatization performance of the banking sector. But no study has either econometrically tested how political constraints affect bank privatization transactions or theretically modeled the privatization transaction. The authors present a simple theoretical framework that models the inherent tradeoffs faced by governments and potential buyers in privatization transactions involving banks. The potential buyer is concerned about the probability that the bank will remain solvent, about the profits it will earn after privatization, and about the price paid for the assets and liabilities. The government is concerned about the price received for the assets, about layoffs, and about service coverage after privatization. The evidence from bank privatization transactions in Argentina in the 1990s supports several of their theoretical predictions. In particular, provinces with high fiscal deficits were willing to accept layoffs and to guarantee a larger part of the privatized banks' portfolio in return for a higher price. The tequila crisis (Mexico's economic crisis in 1994-95) meant that politicians could protect fewer jobs and had to assume a greater share of their public banks' assets. Evidence of better performance at banks privatized after Mexico's crisis suggests that, by tying politicians' hands, the crisis may have brought unforeseen benefits. This conjecture awaits further empirical validation, but the authors hope that by explicitly incorporating the incentives politicians face, analysis can begin to address the question of why some privatizations succeed more than others.